Vinorelbine's anti-tumor actions may depend on the mitotic apoptosis, autophagy and inflammation: hypotheses with implications for chemo-immunotherapy of advanced cancers and pediatric gliomas - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
Vinorelbine is a very potent chemotherapeutic agent which is used to treat a number of cancers including breast and non-small cell lung tumors. Vinorelbine mainly acts via blocking microtubules and induces a specific type of cell death called mitotic catastrophe/apoptosis' subsequent to mitotic slippage, which is the failure of cells to stay in a mitotic arrested state and replicating their DNA without cytokinesis. Glial tumor cells are especially sensitive to mitotic slippage. In recent years, vinorelbine demonstrated potency in pediatric optic and pontine gliomas. In this manuscript, we propose that vinorelbine's anti-tumor actions involve mitotic apoptosis, autophagy and inflammation. Intravenous infusion of vinorelbine induces a peculiar severe pain in the tumor site and patients with highly vascularized, oedematous and necrotic tumors are particularly vulnerable to this pain. Severe pain is a sign of robust inflammation and anti-inflammatory agents are used in treatment of this side effect. However, no one has questioned whether inflammation contributes to anti-tumor effects of vinorelbine, despite the existing data that vinorelbine induces Toll-Like Receptor-4 (TLR4), cytokines and cell death in endothelial cells especially under hypoxia. Robust inflammation may contribute to tumor necrosis such as seen during immunotherapy with lipopolysaccharides (LPS). Evidence also emerges that enhanced cyclooxygenase activity may increase cancer cell death in certain contexts. There are data indicating that non-steroidal anti-inflammatory drugs (NSAIDs) could block anti-tumor efficacy of taxanes, which also work mainly via anti-microtubule actions. Further, combining vinorelbine with immunostimulant cytokines provided encouraging results in far advanced melanoma and renal cell carcinoma, which are highly antigenic tumors. Vinorelbine also showed potential in treatment of inflammatory breast cancer. Finally, pontine gliomas - where partial activity of vinorelbine is shown by some studies - are also tumors which partially respond to immune stimulation. Animal experiments shall be conducted whether TLR4-activating molecules or immune-checkpoint inhibitors could augment anti-tumor actions of vinorelbine. Noteworthy, TLR4-activation seems as the most promising way of cancer immunotherapy, as a high percentage of molecules which demonstrated clinical benefits in cancer treatment are activators of TLR4, including BCG vaccine, monophosphoryl lipid A and picibanil (OKT-432). The provided data would be meaningful for the oncological practice.
Keywords: Vinorelbine; mitotic apoptosis; autophagy; inflammation; immunity; TLR4 agonists; CELL LUNG-CANCER; TUMOR SITE; ENDOPLASMIC-RETICULUM; THERAPEUTIC-EFFICACY; METASTATIC MELANOMA; VINCA ALKALOIDS; PONTINE GLIOMA; ONCOLOGY-GROUP; BREAST-CANCER; ACUTE PAIN